Influence Work Station Design and Firm Constitutional Complaint Against Musculoskeletal on Stone Crusher Worker Progo in Magelang (Universitas Negeri Semarang, 2020)
A rock-breaking work that engaged in the informal sector and contain a great job risk to health and safety of workers. Solving Stone in the river Progo an informal jobs into one livelihood. In working stone crushers appears work attitude accordance with his needs. Work attitude or ergonomic working conditions caused by the design of work stations that were not appropriate in turn can lead to complaints such as disorders of the musculoskeletal system. This research is quantitative, using observational design